Low-temperature sintered metal soldering paste and preparation method and application thereof

By adding sintering aids to the metal solder paste formula and using reducing agent to generate nanometal particles, the performance degradation caused by the high sintering temperature of traditional metal solder paste is solved, and the metal solder paste with low temperature sintering has excellent shear strength and conductivity.

CN119426848AActive Publication Date: 2025-02-14GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411447412.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The sintering temperature of traditional metal solder paste is high, resulting in a decrease in the shear strength and conductivity of interconnected devices. At the same time, high-temperature sintering will also increase the thermal stress of the substrate, chip and solder paste, affecting mechanical properties.

Method used

Low-temperature sintering is achieved by adding sintering aids to the formulation of metal solder paste and reducing the metal salt to nanometal particles using reducing agents to reduce the sintering temperature.

Benefits of technology

Under low-temperature sintering conditions, metal solder paste obtains high shear strength and conductivity, avoiding the thermal stress problems caused by high-temperature sintering, reducing sintering energy consumption, and achieving green sintering.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a low-temperature sintered metal soldering paste and a preparation method and application thereof, and the preparation method comprises the following steps: A, adding a metal salt, a sintering aid and a reducing agent into a solvent, and reacting to obtain a low-temperature sintered metal suspension; wherein the low-temperature sintering metal suspension contains metal nanoparticles, and the sintering temperature of the metal nanoparticles is higher than 300 DEG C; b, concentrating the low-temperature sintered metal turbid liquid in a vacuum environment to obtain low-temperature sintered metal soldering paste; wherein the sintering temperature of the metal soldering paste sintered at the low temperature is 130-240 DEG C. According to the preparation method of the low-temperature sintered metal soldering paste, the preparation method is simple and high in operability, and the obtained metal soldering paste has high shear strength and conductivity on the premise that low-temperature sintering is achieved by adding the sintering aid into the formula.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic manufacturing, and in particular to a low-temperature sintered metal solder paste and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of integrated circuit technology, the internal structure of chips has become increasingly miniaturized and the functions have become more complex, and the requirements for interconnection materials have reached an unprecedented level. When traditional metal solder paste is used as an interconnection material, its sintering temperature is relatively high. Due to the different thermal expansion coefficients of the substrate, chip and solder paste, the high-temperature sintering process will cause the interconnection device formed by the substrate, chip and solder paste to produce large thermal stress, thereby reducing the mechanical properties of the interconnection device, especially the shear strength. In addition, during the high-temperature sintering process, the metal particles in the metal solder paste will undergo changes such as phase change, oxidation or grain coarsening, which will cause the conductive performance of the interconnection device to decrease.

[0003] In order to solve the problem of decreased shear strength and decreased electrical conductivity caused by the high sintering temperature of metal solder paste, the industry has adopted a solution of using thermally conductive adhesive as an interconnection material. Specifically, the curing temperature of thermally conductive adhesive is generally low (lower than 150°C), which can effectively prevent the chip from being affected by high temperature during the interconnection process. However, since the base resin of the thermally conductive adhesive is an insulator, its electrical conductivity is poor. Although its electrical conductivity can be improved by adding conductive fillers (such as metal particles and carbon black, etc.), the improvement in electrical conductivity achieved by the above means is often limited. At the same time, since the thermal expansion coefficient of the base resin is high and the thermal conductivity is relatively low, during the curing process, it is easy to cause the interconnection device formed by the substrate, chip and thermally conductive adhesive to produce greater thermal stress, which reduces the shear strength of the interconnection device. That is, although the conductive adhesive used as the interconnection material in the prior art can reduce the interconnection temperature, it still cannot meet the requirements of the interconnection device for shear strength and electrical conductivity. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a low-temperature sintered metal solder paste. The preparation method is simple and easy to operate. By adding a sintering aid to the formula, the obtained metal solder paste has high shear strength and conductive properties while achieving low-temperature sintering, thereby overcoming the shortcomings of the prior art.

[0005] Another object of the present invention is to provide a low-temperature sintered metal solder paste prepared by the above preparation method, which can not only be sintered at low temperature but also has excellent shear strength and electrical conductivity.

[0006] The third object of the present invention is to provide an application of a low-temperature sintered metal solder paste, which is used in the preparation of interconnection devices to ensure that the obtained interconnection devices have good shear strength and conductive properties.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A method for preparing a low-temperature sintered metal solder paste comprises the following steps:

[0009] A. adding a metal salt, a sintering aid and a reducing agent into a solvent, and reacting to obtain a low-temperature sintered metal suspension; wherein the low-temperature sintered metal suspension contains metal nanoparticles, and the sintering temperature of the metal nanoparticles is greater than 300° C.;

[0010] B. Concentrating the low-temperature sintered metal suspension under a vacuum environment to obtain a low-temperature sintered metal solder paste; wherein the sintering temperature of the low-temperature sintered metal solder paste is 130-240°C.

[0011] Furthermore, in step A, the molar ratio of the metal salt to the reducing agent is 1:(1-10); the molar ratio of the metal salt to the sintering aid is 1:(0.001-0.05).

[0012] Furthermore, in step A, the particle size of the metal nanoparticles is 80 to 1200 nm.

[0013] Further, in step A, the metal salt is any one of a copper salt and a silver salt;

[0014] The sintering aid includes any one or more combinations of (BiO)2CO3, Bi(OH)3, Bi(C2H3O2)3, Bi2O3, Bi(NO3)3, Bi2(SO4)3, TiO2, Bi, and Ce.

[0015] Further, in step A, the copper salt is any one of copper acetate, copper hydroxide, copper formate, copper carbonate, copper bicarbonate, copper acetylacetonate or copper oxalate;

[0016] The silver salt is any one of silver acetate, silver hydroxide, silver formate, silver carbonate, silver bicarbonate, silver acetylacetonate or silver oxalate;

[0017] The reducing agent is any one or more of hydrazine hydrate, ascorbic acid, glucose, phenylhydrazine and citric acid;

[0018] The solvent is any one or more combinations of water, toluene, ether, ethyl acetate, ethanol, ethylene glycol, diethylene glycol, diethylene glycol, dipropylene glycol, glycerol, acetone, glycerin, terpineol and polyethylene glycol.

[0019] Furthermore, in step A, the reaction temperature of the reaction is 15 to 100° C., and the reaction time is 5 to 180 min.

[0020] Furthermore, in step B, the content of the nano metal particles in the low-temperature sintered metal solder paste is 20-99% calculated by mass percentage.

[0021] Furthermore, step A specifically includes:

[0022] A1. Adding a metal salt and a sintering aid to a portion of the solvent, stirring to obtain a first mixture;

[0023] A2. Adding the reducing agent to the remaining amount of the solvent, stirring to obtain a second mixture;

[0024] A3. The first mixed material and the second mixed material are reacted to obtain a low-temperature sintered metal suspension.

[0025] A low-temperature sintered metal solder paste is prepared using the above-mentioned method for preparing the low-temperature sintered metal solder paste.

[0026] The invention discloses an application of a low-temperature sintered metal solder paste in preparing an interconnection device. The method uses the low-temperature sintered metal solder paste, and comprises the following steps: coating the low-temperature sintered metal solder paste on a substrate; covering an interconnection chip on the surface of the coated low-temperature sintered metal solder paste, and sintering the chip under the conditions of a sintering temperature of 130-240°C and a sintering pressure of 0-50Mpa to obtain an interconnection device.

[0027] The technical solution provided by the present invention may include the following beneficial effects:

[0028] 1. In this technical solution, a reducing agent is used to reduce metal salts into nano-metal particles. The characteristics of easy aggregation and short diffusion distance of nano-metal particles are utilized to make the metal solder paste prepared by using nano-metal particles have a lower sintering temperature. This not only reduces the sintering energy consumption of the metal solder paste and realizes green sintering, but also avoids the technical problem that the shear strength and conductivity of the metal solder paste are easily affected by the high sintering temperature, thereby ensuring its shear strength and conductivity.

[0029] 2. In this technical solution, by adding a sintering aid, it is not only beneficial to reduce the sintering temperature of the metal solder paste, but also through the sintering aid's role in reducing the sintering temperature, providing additional surface active sites, and promoting diffusion, the shear strength and conductivity of the metal solder paste can be provided. DETAILED DESCRIPTION

[0030] The present technical solution provides a method for preparing a low-temperature sintered metal solder paste, comprising the following steps:

[0031] A. adding a metal salt, a sintering aid and a reducing agent into a solvent, and reacting to obtain a low-temperature sintered metal suspension; wherein the low-temperature sintered metal suspension contains metal nanoparticles, and the sintering temperature of the metal nanoparticles is greater than 300° C.;

[0032] B. Concentrating the low-temperature sintered metal suspension under a vacuum environment to obtain a low-temperature sintered metal solder paste; wherein the sintering temperature of the low-temperature sintered metal solder paste is 130-240°C.

[0033] In order to solve the technical problem in the prior art that the curing temperature of the thermal conductive adhesive is low but the shear strength and conductivity are poor, the present technical solution proposes a method for preparing a low-temperature sintered metal solder paste, which simplifies the preparation steps, controls the preparation conditions, combines the use of a reducing agent to reduce the metal salt to nano-metal particles and adds a sintering aid to the metal solder paste formula, so that the obtained metal solder paste has high shear strength and conductivity while achieving low-temperature sintering, so as to meet actual use requirements.

[0034] Specifically, in order to solve the technical problems caused by the high sintering temperature of metal solder paste, the industry has adopted thermal conductive adhesive as interconnection material. However, although the conductive adhesive used as interconnection material in the prior art can reduce the interconnection temperature, it still cannot meet the requirements of interconnection devices for shear strength and conductivity. The technical solution first uses a reducing agent to reduce the metal salt to nano metal particles, and the particle size of the nano metal particles is extremely small, and has a high surface energy and surface activity. The above high surface energy and surface activity make the nano metal particles more likely to aggregate when they contact each other, promote the sintering of the nano metal particles, and make the nano metal particles have a lower sintering temperature. The sintering temperature of the metal solder paste depends on the sintering temperature of the nano metal particles. Therefore, the lower sintering temperature of the nano metal particles makes the metal solder paste prepared by using the nano metal particles have a lower sintering temperature. In addition, compared with the larger metal particles in the traditional metal solder paste, the diffusion distance between the nano metal particles is shorter, which also makes the metal solder paste prepared by the nano metal particles can be sintered and densified at a lower temperature. That is, in the present technical scheme, the metal salt is reduced to nano-metal particles by utilizing a reducing agent, and the characteristics of nano-metal particles that are easy to aggregate and have a short diffusion distance are utilized, so that the metal solder paste prepared using the nano-metal particles has a lower sintering temperature. This not only reduces the sintering energy consumption of the metal solder paste and realizes green sintering, but also avoids the technical problem that the shear strength and conductivity of the metal solder paste are easily affected by the high sintering temperature, thereby ensuring its shear strength and conductivity.

[0035] Secondly, although the nano-metal particles have a lower sintering temperature due to their easy aggregation and short diffusion distance, thus making the metal solder paste have a lower sintering temperature, the sintering temperature of metal nano-particles is generally high, generally greater than 300°C, so the sintering temperature of the metal solder paste is also greater than 300°C, and the above sintering temperature range still makes the nano-metal particles at risk of being oxidized. And when the nano-metal particles are oxidized to metal oxides, since the metal oxides have a higher melting point than the nano-metal particles, the metal oxides will hinder sintering, resulting in the metal oxides and the nano-metal particles themselves not being easy to sinter together, making the solder paste sintered body formed after the metal solder paste is sintered relatively loose, thereby reducing its shear strength and conductivity, and still cannot meet the application places with high requirements for shear strength and conductivity.

[0036] In order to further reduce the sintering temperature of the metal solder paste, the present technical solution specifically adds a sintering aid to the metal solder paste formula, and utilizes the activation effect of the sintering aid to reduce the energy threshold required for the sintering of the nano-metal particles, so that the sintering temperature of the metal solder paste is greatly reduced, and sintering is achieved within a temperature range of 130 to 240°C, which not only greatly reduces the sintering energy consumption of the metal solder paste and achieves green sintering, but also effectively avoids the situation where the nano-metal particles are easily oxidized and hinder sintering when the sintering temperature is high, thereby affecting the shear strength and conductivity. Furthermore, the sintering aid can provide additional surface active sites for the nano-metal particles during the sintering process, promote the interaction and bonding between the nano-metal particles, and effectively improve the density of the solder paste sintered body formed after the metal solder paste is sintered, thereby improving the shear strength and conductivity of the metal solder paste. In addition, the sintering aid also helps to evenly disperse the metal nanoparticles in the metal solder paste, avoids the agglomeration of the metal nanoparticles, and makes it easier for the metal nanoparticles to form a dense solder paste sintered body during the sintering process, which is also beneficial to improving the shear strength and conductivity of the metal solder paste. That is, in this technical solution, by adding a sintering aid, it is not only beneficial to reduce the sintering temperature of the metal solder paste, but also through the sintering aid's role in reducing the sintering temperature, providing additional surface active sites, and promoting diffusion, the shear strength and conductivity of the metal solder paste can be improved.

[0037] Again, in step A of the present technical solution, metal salt, sintering aid, and reducing agent are added to the solvent, that is, in the process of reducing the metal salt to metal nanoparticles, the metal nanoparticles generated by the reaction are surrounded by the solvent, which reduces the possibility of contact with the outside air, thereby reducing the possibility of oxidation of the metal nanoparticles, which is beneficial to ensure the performance of the metal solder paste. In addition, in step B of the present technical solution, the low-temperature sintered metal suspension is concentrated under a vacuum environment, which also reduces the possibility of oxidation of the nano-metal particles in the low-temperature sintered metal suspension during the concentration process, which is also beneficial to ensure the performance of the metal solder paste.

[0038] Finally, the preparation method of metal solder paste in the prior art is usually a liquid phase reduction method. The preparation method of metal solder paste by liquid phase reduction method generally includes the following steps: (1) mixing a precursor metal salt, a reducing agent, a dispersant or a protective agent in a liquid phase to obtain a nano-metal particle liquid phase; (2) separating the liquid phase and the nano-metal particle liquid phase; (3) preparing a metal solder paste. However, the above step (2) includes multiple cleaning and separation of the nano-metal particles, which not only makes the preparation process quite cumbersome, but also causes the nano-metal particles to be exposed to the air multiple times, aggravating the agglomeration and oxidation of the nano-metal particles. In the present technical solution, the preparation of the metal solder paste can be achieved by using the two steps of step A (reduction reaction) and step B (vacuum concentration), without the need to centrifuge, wash and dry the nano-metal particles separately. This not only greatly simplifies the preparation process of the metal solder paste, but also reduces the possibility of agglomeration and oxidation of the nano-metal particles when exposed to the air, thereby ensuring the performance of the metal solder paste.

[0039] Preferably, in step B, the concentration method includes any one of centrifugal separation, evaporation concentration and drying concentration.

[0040] The technical solution limits the concentration methods to multiple types, which is conducive to selecting a suitable centrifugation method according to actual needs, thereby improving the flexibility of the concentration method.

[0041] Preferably, in step B, the concentration method is centrifugal separation, the centrifugal separation speed is 8000-12000 rpm, and the centrifugal time is 1-30 min.

[0042] The preferred concentration method of the present technical solution is centrifugal separation, and the speed and time of centrifugal separation are limited, which is beneficial to improving the concentration effect and thus beneficial to ensuring the performance of the metal solder paste.

[0043] Further, in step A, the molar ratio of the metal salt to the reducing agent is 1:(1-10); the molar ratio of the metal salt to the sintering aid is 1:(0.001-0.05).

[0044] When the molar ratio of the metal salt to the reducing agent is too low, the metal salt cannot be completely reduced to nano metal particles, which is not conducive to ensuring the performance of the metal solder paste; when the molar ratio of the metal salt to the reducing agent is too high, the production cost is too high, resulting in unnecessary waste. Therefore, by limiting the molar ratio of the metal salt to the reducing agent, the performance of the metal solder paste can be ensured at a lower cost.

[0045] When the molar ratio of the metal salt to the sintering aid is too low, the conductive properties of the metal solder paste are easily affected due to the high content of the sintering aid; when the content of the sintering aid is too low, the effect of reducing the sintering temperature of the metal solder paste is limited. Therefore, the technical solution limits the molar ratio of the metal salt to the sintering aid, so as to ensure the performance of the metal solder paste while reducing the sintering temperature of the metal solder paste.

[0046] Preferably, the molar ratio of the metal salt to the reducing agent is 1:(2-8).

[0047] By further limiting the molar ratio of the metal salt to the reducing agent, not only can the metal salt be completely reduced to nano-metal particles, but even if the nano-metal particles are oxidized to metal oxides during the preparation process, the metal oxides can be reduced as much as possible, thereby better ensuring the performance of the metal solder paste.

[0048] Further, in step A, the particle size of the metal nanoparticles is 80 to 1200 nm.

[0049] The smaller the particle size of the metal nanoparticles, the smaller the sintering energy required. However, when the particle size of the metal nanoparticles is too small, they are prone to oxidation and agglomeration, resulting in an increase in the sintering temperature of the metal solder paste and a decrease in performance. When the particle size of the metal nanoparticles is too large, the sintering temperature of the metal solder paste is easily increased. Therefore, in this technical solution, the particle size of the metal nanoparticles is limited to 80 to 1200 nm, which is conducive to ensuring the performance and sintering temperature of the metal solder paste.

[0050] Further, in step A, the metal salt is any one of a copper salt and a silver salt;

[0051] The sintering aid includes any one or more combinations of (BiO)2CO3, Bi(OH)3, Bi(C2H3O2)3, Bi2O3, Bi(NO3)3, Bi2(SO4)3, TiO2, Bi, and Ce.

[0052] Since copper salt and silver salt are both cheap, and the nano copper particles after copper salt reduction and the nano silver particles after silver salt reduction both have good conductivity, the technical solution limits the metal salt to any one of copper salt and silver salt.

[0053] Furthermore, since (BiO)2CO3, Bi(OH)3, Bi(C2H3O2)3, Bi2O3, Bi(NO3)3, Bi2(SO4)3, TiO2, Bi, and Ce can all promote low-temperature sintering, the technical solution preferably selects the sintering aid as any one or more combinations of (BiO)2CO3, Bi(OH)3, Bi(C2H3O2)3, Bi2O3, Bi(NO3)3, Bi2(SO4)3, TiO2, Bi, and Ce. In addition, the sintering aids (BiO)2CO3, Bi(OH)3, Bi(C2H3O2)3, Bi(NO3)3, and Bi2(SO4)3 all generate Bi2O3 after sintering, and both TiO2 and Bi2O3 have good sintering activity and wettability, which help to promote the bonding between nano-metal particles, thereby improving the shear strength and conductivity of the metal solder paste after sintering. Bi can not only reduce the sintering temperature, but also help fill the gaps between nano-metal particles, which is beneficial to improve the shear strength and conductivity of metal solder paste. In addition, Bi can also form alloys with other nano-metal particles to improve the corrosion resistance of metal solder paste after sintering. Ce can not only reduce the sintering temperature, but also Ce plays a catalytic role in the sintering process, reducing the activation energy of the sintering reaction, thereby accelerating the sintering process.

[0054] Further, in step A, the copper salt is any one of copper acetate, copper hydroxide, copper formate, copper carbonate, copper bicarbonate, copper acetylacetonate or copper oxalate;

[0055] The silver salt is any one of silver acetate, silver hydroxide, silver formate, silver carbonate, silver bicarbonate, silver acetylacetonate or silver oxalate;

[0056] The reducing agent is any one or more of hydrazine hydrate, ascorbic acid, glucose, phenylhydrazine and citric acid;

[0057] The solvent is any one or more combinations of water, toluene, ether, ethyl acetate, ethanol, ethylene glycol, diethylene glycol, diethylene glycol, dipropylene glycol, glycerol, acetone, glycerin, terpineol and polyethylene glycol.

[0058] By preferably including multiple types of copper salts, silver salts, reducing agents and solvents, not only can the performance of the metal solder paste be ensured, but also suitable raw materials can be selected according to actual needs, providing more possibilities and flexibility for its application in different fields.

[0059] Further, in step A, the reaction temperature of the reaction is 15 to 100° C., and the reaction time is 5 to 180 min.

[0060] By optimizing the reaction temperature and reaction time, the metal salt can be reduced as much as possible and the sintering aid can fully play its role, thereby reducing production costs and improving production efficiency while ensuring the performance of the metal solder paste.

[0061] Further, in step B, the content of the nano metal particles in the low-temperature sintered metal solder paste is 20-99% calculated by mass percentage.

[0062] Calculated by mass percentage, the content of nano metal particles in the low-temperature sintered metal solder paste is 20-99%, so that metal solder pastes with different nano metal particle contents can be selected according to actual application requirements, thereby improving its practicability.

[0063] To further illustrate, step A specifically includes:

[0064] A1. Adding a metal salt and a sintering aid to a portion of the solvent, stirring to obtain a first mixture;

[0065] A2. Adding the reducing agent to the remaining amount of the solvent, stirring to obtain a second mixture;

[0066] A3. The first mixed material and the second mixed material are reacted to obtain a low-temperature sintered metal suspension.

[0067] By optimizing step A, the metal salt, the sintering aid and the reducing agent are fully dissolved and dispersed, which is beneficial to ensure the performance of the metal solder paste.

[0068] A low-temperature sintered metal solder paste is prepared using the above-mentioned method for preparing the low-temperature sintered metal solder paste.

[0069] The present invention also provides a method for preparing a low-temperature sintered metal solder paste. The low-temperature sintered metal solder paste prepared can not only be sintered at a low temperature, but also has excellent shear strength and electrical conductivity.

[0070] The invention discloses an application of a low-temperature sintered metal solder paste in preparing an interconnection device. The method uses the low-temperature sintered metal solder paste, and comprises the following steps: coating the low-temperature sintered metal solder paste on a substrate; covering an interconnection chip on the surface of the coated low-temperature sintered metal solder paste, and sintering the chip under the conditions of a sintering temperature of 130-240°C and a sintering pressure of 0-50Mpa to obtain an interconnection device.

[0071] The technical solution also proposes an application of a low-temperature sintered metal solder paste in the preparation of an interconnect device, comprising the following steps: coating the low-temperature sintered metal solder paste on a substrate, covering the surface of the coated low-temperature sintered metal solder paste with an interconnect chip, and sintering at a sintering temperature of 130 to 240°C and a sintering pressure of 0 to 50 MPa to obtain an interconnect device, thereby ensuring that the obtained interconnect device has good shear strength and conductivity.

[0072] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0073] Performance Test:

[0074] (1) Shear strength: A low-temperature sintered metal solder paste is coated on a substrate, and an interconnection chip is placed on the surface of the coated low-temperature sintered metal solder paste. The interconnection device is sintered to obtain an interconnection device. The shear strength of the interconnection device is tested using an IC packaging welding strength tester (SERIES-4000-DONDESTER). When the shear strength is greater than 40 MPa, it is qualified.

[0075] (2) Conductivity: A low-temperature sintered metal solder paste is coated on a substrate, and an interconnection chip is placed on the surface of the coated low-temperature sintered metal solder paste. The interconnection device is sintered to obtain the surface resistivity of the interconnection device. The surface resistivity of the interconnection device is tested using a ST-2258C four-probe tester. When the resistivity is <15×10 -8 Ω.m, which means it is qualified.

[0076] Example 1

[0077] A. Add copper carbonate and Bi(OH)3 into 100 mL of ethanol and stir to obtain a first mixture; add hydrazine hydrate into 100 mL of ethanol and stir to obtain a second mixture; react the first mixture and the second mixture at 80°C for 30 minutes to obtain a low-temperature sintered metal suspension; wherein the low-temperature sintered metal suspension contains copper nanoparticles with a particle size of 800 nm, and the sintering temperature of the copper nanoparticles is 330°C; the molar ratio of copper carbonate to hydrazine hydrate is 1:5; the molar ratio of copper carbonate to Bi(OH)3 is 1:0.02; the content of nano metal particles in the low-temperature sintered metal solder paste is 30%;

[0078] B. The low-temperature sintered metal suspension is centrifuged under vacuum to obtain a low-temperature sintered metal solder paste; wherein the sintering temperature of the metal solder paste is 180° C.; the centrifugal separation speed is 10000 rpm, and the centrifugal time is 20 min.

[0079] Example 2

[0080] A. Add silver acetate and Bi2O3 to 120 mL of glycerol and stir to obtain a first mixture; add ascorbic acid to 80 mL of glycerol and stir to obtain a second mixture; react the first mixture and the second mixture at 100° C. for 20 min to obtain a low-temperature sintered metal suspension; wherein the low-temperature sintered metal suspension contains silver nanoparticles with a particle size of 500 nm, and the sintering temperature of the silver nanoparticles is 310° C.; the molar ratio of silver acetate to ascorbic acid is 1:4; the molar ratio of silver acetate to Bi2O3 is 1:0.001; the content of nanosilver particles in the low-temperature sintered metal solder paste is 50%;

[0081] B. The low-temperature sintered metal suspension is centrifuged under vacuum to obtain a low-temperature sintered metal solder paste; the sintering temperature of the metal solder paste is 220° C. The centrifugal separation speed is 8000 rpm and the centrifugal time is 10 min.

[0082] Example 3

[0083] A. Add copper hydroxide and TiO2 to 140 mL of diethylene glycol, and stir to obtain a first mixture; add citric acid to 60 mL of diethylene glycol, and stir to obtain a second mixture; react the first mixture and the second mixture at 60° C. for 90 minutes to obtain a low-temperature sintered metal suspension; wherein the low-temperature sintered metal suspension contains copper nanoparticles with a particle size of 1200 nm, and the sintering temperature of the copper nanoparticles is 360° C.; the molar ratio of copper hydroxide to citric acid is 1:6; the molar ratio of copper hydroxide to TiO2 is 1:0.05; the content of nano metal particles in the low-temperature sintered metal solder paste is 80%;

[0084] B. The low-temperature sintered metal suspension is centrifuged under vacuum to obtain a low-temperature sintered metal solder paste; the sintering temperature of the metal solder paste is 240° C. The centrifugal separation speed is 12000 rpm, and the centrifugal time is 30 min.

[0085] Comparative Example 1

[0086] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that no sintering aid is added in Comparative Example 1.

[0087] The metal solder pastes prepared by the preparation methods of Examples 1-3 and Comparative Example 1 were used to prepare interconnection devices, and the performance of the prepared interconnection devices was tested. When other conditions were the same, the interconnection devices were compared with those prepared by traditional conductive adhesives and traditional metal solder pastes. The specific test results are shown in Table 1:

[0088] Table 1 Performance test results of different interconnect devices

[0089] Performance test items Shear strength(MPa) Conductivity(Ω.m) Example 1 60.98 <![CDATA[13.64×10 -8 ]]> Example 2 58.63 <![CDATA[13.91×10 -8 ]]> Example 3 54.32 <![CDATA[14.18×10 -8 ]]> Comparative Example 1 38.17 <![CDATA[18.48×10 -8 ]]> Traditional conductive adhesive 37.49 <![CDATA[19.73×10 -8 ]]> Traditional metal solder paste 39.75 <![CDATA[17.04×10 -8 ]]>

[0090] From the test results in Table 1, it can be seen that the shear strength of the interconnection device prepared by the low-temperature sintered metal solder paste of the present technical solution is greater than 40MPa, and the resistivity is less than 15×10 -8 Ω.m, and its various properties are better than those of the interconnection devices prepared by the conventional conductive adhesive and the conventional metal solder paste, that is, the existing interconnection devices have high shear strength and conductivity, and when other conditions are the same, the shear strength and conductivity of the interconnection devices depend on the shear strength and conductivity of the metal solder paste. Therefore, the metal solder paste obtained by the technical solution has high shear strength and guidance, which can break through the functional limitations of the conventional conductive adhesive and the conventional metal solder paste, and solve the technical problem that the conventional conductive adhesive and the conventional metal solder paste have poor shear strength and guidance and cannot meet the actual use requirements.

[0091] Since no sintering aid is added to comparative example 1, the shear strength and conductivity are reduced; at the same time, since no sintering aid is added, it cannot be completely sintered at low temperature, which further affects the shear strength and conductivity, so that the shear strength and conductivity of the obtained interconnect device are poor and cannot meet the use requirements.

[0092] It should be noted that, calculated by mass, the traditional conductive adhesive includes 50-80 parts of silver powder, 1-2 parts of coupling agent, 10-20 parts of graphene, 3-5 parts of sodium dodecylaminopropionate, 3-5 parts of dimethyldichlorosilane, 2-3 parts of curing agent, 2-3 parts of accelerator, 2-3 parts of bail agent, 1-2 parts of preservative, 20-35 parts of polymer cellulose and 10-35 parts of conductive fiber.

[0093] Calculated by mass percentage, traditional metal solder paste includes 80-92% brazing powder and 8-20% binder; calculated by mass percentage, brazing powder includes 10-30% nano silver powder, 60-80% silver-copper alloy powder, 5-10% aluminum-silicon alloy powder / titanium-aluminum alloy powder and 2-5% titanium hydride powder; calculated by mass percentage, the binder includes 75-90% solvent, 5-10% thickener, 2-4% surfactant, 1-2% dispersant and 2-5% thixotropic agent.

[0094] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a low-temperature sintered metal solder paste, characterized in that: The following steps are involved: A. adding a metal salt, a sintering aid and a reducing agent into a solvent, and reacting to obtain a low-temperature sintered metal suspension; wherein the low-temperature sintered metal suspension contains metal nanoparticles, and the sintering temperature of the metal nanoparticles is greater than 300° C.; B. Concentrating the low-temperature sintered metal suspension under a vacuum environment to obtain a low-temperature sintered metal solder paste; wherein the sintering temperature of the low-temperature sintered metal solder paste is 130-240°C.

2. The method for preparing a low-temperature sintered metal solder paste according to claim 1, characterized in that: In step A, the molar ratio of the metal salt to the reducing agent is 1:(1-10); the molar ratio of the metal salt to the sintering aid is 1:(0.001-0.05).

3. The method for preparing a low-temperature sintered metal solder paste according to claim 1, characterized in that: In step A, the particle size of the metal nanoparticles is 80 to 1200 nm.

4. The method for preparing a low-temperature sintered metal solder paste according to claim 1, characterized in that: In step A, the metal salt is any one of a copper salt and a silver salt; The sintering aid includes any one or more combinations of (BiO)2CO3, Bi(OH)3, Bi(C2H3O2)3, Bi2O3, Bi(NO3)3, Bi2(SO4)3, TiO2, Bi, and Ce.

5. The method for preparing a low-temperature sintered metal solder paste according to claim 1, characterized in that: In step A, the copper salt is any one of copper acetate, copper hydroxide, copper formate, copper carbonate, copper bicarbonate, copper acetylacetonate or copper oxalate; The silver salt is any one of silver acetate, silver hydroxide, silver formate, silver carbonate, silver bicarbonate, silver acetylacetonate or silver oxalate; The reducing agent is any one or more of hydrazine hydrate, ascorbic acid, glucose, phenylhydrazine and citric acid; The solvent is any one or more combinations of water, toluene, ether, ethyl acetate, ethanol, ethylene glycol, diethylene glycol, diethylene glycol, dipropylene glycol, glycerol, acetone, glycerin, terpineol and polyethylene glycol.

6. The method for preparing a low-temperature sintered metal solder paste according to claim 1, characterized in that: In step A, the reaction temperature of the reaction is 15-100° C., and the reaction time is 5-180 min.

7. The method for preparing a low-temperature sintered metal solder paste according to claim 1, characterized in that: In step B, the content of the nano metal particles in the low-temperature sintered metal solder paste is 20-99% calculated by mass percentage.

8. The method for preparing a low-temperature sintered metal solder paste according to claim 1, characterized in that: Step A specifically includes: A1. Adding a metal salt and a sintering aid to a portion of the solvent, stirring to obtain a first mixture; A2. The reducing agent is added to the remaining amount of the solvent and stirred to obtain a second mixture; A3. The first mixed material and the second mixed material are reacted to obtain a low-temperature sintered metal suspension.

9. A low temperature sintered metal solder paste, characterized in that: The solder paste is prepared by the method for preparing a low-temperature sintered metal solder paste as described in any one of claims 1 to 8.

10. Application of a low-temperature sintered metal solder paste in the preparation of interconnection devices, characterized in that: The use of the low-temperature sintered metal solder paste as described in claim 9 includes the following steps: coating the low-temperature sintered metal solder paste on a substrate; covering the surface of the coated low-temperature sintered metal solder paste with an interconnection chip, and sintering at a sintering temperature of 130 to 240° C. and a sintering pressure of 0 to 50 MPa to obtain an interconnection device.

Citation Information

Patent Citations

  • Nanometer tin-bismuth composite welding paste and preparation method

    CN107877030A

  • Alloy nanometer particle soldering paste and preparation method thereof

    CN109352206A

  • Multi-size micro-nano metal particle soldering paste in-situ interconnection process and product thereof

    CN113385857A

  • Flux compositions for sintering Ni-Zn ferrite material

    US20050034633A1